The interplay between formal and informal elements in analysing situations of role conflict among construction participants. Issue 12 (2nd December 2018) - Kabiri, Shabnam; Hughes, Will
Abstract: The interplay of formal and informal factors in construction teams influences the enactment of roles and the individuals who fulfil those roles. With a specific focus on a phenomenon called role conflict, the aim is to explore if and how the interaction of formal and informal elements would lead to situations of role conflict. This phenomenon proved to lead to frustration, tension and employee burnout. An analytical model of role interaction was developed, which disentangles formal and informal elements that shape role interactions. Qualitative data was collected through semi-structured interviews, project documents and observations. Four cases of role conflict are presented here. Contract, as a formal element, and participant's values and interests, as informal elements, appeared to be the most important factor shaping participants' expectations and behaviours. The analysis in this study showed that if a participant who faces role conflict is able to influence the formal elements in favour of his or her informal elements, then he or she may experience less frustration. At a more general level, the results suggest that increasing formality can increase participants' frustration, which then would decrease the likelihood of collaboration. As the theoretical contribution, this research extends organizational role theory to deal with informal and formal aspects. Taking into account formal sources enables the study of how roles are institutionally governed while including informal sources allows for the idea that some of the aspects of the role, even in the context of work role, are socially constructed.